Experimental hydrothermal characteristics of concentric tube heat exchanger with V-cut twisted tape turbulator using PCM dispersed mono/hybrid nanofluids - Singh S.K.; Sarkar J. (My University, 2025)
Impact of using V-cuts twisted tape insert and phase change material (PCM) dispersed mono or hybrid nanofluid on the hydrothermal characteristics of the double tube heat exchanger is experimentally investigated. Water-based Al2O3 and PCM nanofluids and Al2O3+ PCM hybrid nanofluid with different concentrations are used in inner tube. Influences of various geometric parameters of V-cuts twisted tape insert on heat transfer, pressure drop and entropy generation are investigated. Results reveal that heat transfer and pressure drop increase with the increase in particle concentration and decrease in twisting ratio. A higher V-cut depth ratio or lower width ratio yields more heat transfer and pressure drop. © 2020 Taylor & Francis.